PrEP in the Context of Other HIV Risk Reduction Strategies Among Men Who Have Sex with Men: Results from the Flash! PrEP in Europe Survey - Di Ciaccio, Marion (2022)
Combination HIV prevention covers a range of biomedical, behavioral, and socio-structural interventions. Despite the growing availability of pre-exposure prophylaxis (PrEP), it is not always accessible in European Centre for Disease Prevention and Control reporting countries and may not meet the needs of all at-risk populations. Based on the Flash! PrEP in Europe data, multiple correspondence analysis and hierarchical clustering were used to identify patterns in HIV prevention strategies among 9980 men who have sex with men (MSM). PrEP interest was evaluated among four identified clusters: (A) “high condom use, sometimes Treatment as Prevention (TasP)”; (B) “mix of methods, infrequent condom use”; (C) “high condom use, tendency to choose partners based on serological status” and (D) “moderate use of condoms mixed with other prevention strategies”. Clusters B and D had higher PrEP interest. These results suggest that MSM use a range of behavioral and biomedical risk reduction strategies that are often combined. On-demand PrEP may meet the needs of MSM who infrequently use condoms and other prevention methods.